Analisis Faktor Yang Mempengaruhi Kualitas Laporan Keuangan Pada Pelaku UMKM di Kota Bengkulu - Debby Arisandi; Aan Shar; Meydina Putri (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
This study aims to determine the factors that affect the quality of financial reports for MSME actors in Bengkulu City based on the Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM) which are the current financial reporting standards for MSMEs. Bookkeeping of business activities is a financial report that separates business assets from non-business assets, there are still many MSME actors who have not made books in accordance with standards. In general, MSME actors keep simple financial records so that these records do not reflect the actual financial status of the business. Many MSME actors are still negligent in preparing their business financial statements, making it difficult to get financing from banks. Financial reports are needed to determine the company's profit or loss, assets, liabilities, and capital control, as well as planning for the efficiency of expenditures that occur, all of which act as decision-making tools for business development. The study used three independent variables, namely Education Level (X1), Business Scale (X2), Business Length (X3), and one dependent variable, namely the quality of financial reports. The sample of MSMEs studied were MSMEs in Singaran Pati District, Bengkulu City with a total population of 344 MSMEs. The results of the study show that the variables of education level, business scale and length of business are factors that affect the quality of financial reports for MSME actors in Bengkulu City. From the results of the analysis of data testing on these 3 variables, the MSA value for education level has an MSA value of 0.683, Business scale has an MSA value of 0.698, and the length of business has an MSA value of 0.674.